Shewanella baltica strain JD0705 isolated from the mangrove wetland soils in Thailand and characterization of its ligninolytic performance - Aiya Chantarasiri (Society for Indonesian Biodiversity, 2021)
Abstract. Chantarasiri A. 2021. Shewanella baltica strain JD0705 isolated from the mangrove wetland soils in Thailand and characterization of its ligninolytic performance. Biodiversitas 22: 354-361. Lignin is a complex biopolymer and the third component by mass of lignocellulosic plant biomass. Its recalcitrant property hampers the hydrolysis and utilization of cellulose and hemicellulose in the lignocellulosic biomass. Thus, the delignification of lignocellulosic biomass is an enormous challenge for emerging bio-based applications. This study presented a potential ligninolytic bacterium for potential use in the biological delignification process under mild conditions. This bacterium was isolated from the mangrove wetland soils in Thailand, characterized and identified as psychrotrophic Shewanella baltica strain JD0705. It was determined for ligninolytic activity and showed laccase activity at 5.23 ± 0.10 U/mL. The optimum temperature and pH for the laccase activity were observed to be 25°C at a pH of 7.0 respectively with a stability range of 20-30°C temperature and pH of 7.0-8.0. S. baltica strain JD0705 was used in the biological delignification of rice husk powder and promoted the hydrolysis of rice husk powder to obtain more liberating sugar content. The findings from this study indicated that feasibility of using this ligninolytic bacterium for the production of laccase and the delignification of lignocellulosic plant biomass.